Anti-BLV antibodies in whey correlate with bovine leukemia virus disease progression and BoLA-DRB3 polymorphism - Nakatsuchi, Ayumi; Bao, Aronggaowa; Watanuki, Sonoko; Matsuura, Ryosuke; Borjigin, Liushiqi; Bai, Lanlan; Kuroda, Maho; Matsumoto, Yasunobu; Kohara, Junko; Aida, Yoko (Frontiers in Veterinary Science, 2022)
Bovine leukemia virus (BLV) belongs to the family Retroviridae and is a causative agent for enzootic bovine leucosis, the most common neoplastic disease affecting cattle worldwide. BLV proviral load (PVL) is associated with disease progression and transmission risk but requires blood collection and quantitative PCR testing. Anti-BLV antibodies in whey have been used as a diagnostic tool for BLV infection; however, quantitative utilization has not been fully investigated. Furthermore, bovine leukocyte antigen (BoLA)-DRB3 is a polymorphic gene associated with BLV infectivity and PVL, but its effect on anti-BLV antibody levels in whey from BLV infected dams is unknown. Therefore, we aimed to investigate whether it is possible to correctly predict PVL in the blood and milk based on the amount of anti-BLV antibodies in milk, and whether the BoLA-DRB3 alleles associate with the amount of anti-BLV antibodies in milk. We examined whey from 442 dams from 11 different dairy farms located in 6 prefectures in Japan, including susceptible dams carrying at least one BoLA-DRB3*012:01 or *015:01 allele related with high PVL, resistant dams carrying at least one BoLA-DRB3*002:01, *009:02, or *014:01:01 allele related with low PVL, and neutral dams carrying other alleles. First, our results provided compelling evidence that anti-BLV antibody levels in whey were positively correlated with the anti-BLV antibody levels in serum and with BLV PVL in blood and milk, indicating the possibility of estimating BLV PVL in blood and milk by measuring anti-BLV antibody levels in whey. Thus, our results showed that antibody titers in milk might be effective for estimating BLV transmission risk and disease progression in the field. Second, we demonstrated that anti-BLV antibody levels in whey from BLV resistant dams were significantly lower than those from susceptible and neutral dams. This is the first report suggesting that the BoLA-DRB3 polymorphism affects anti-BLV antibody levels in whey from BLV-infected dams. Taken together, our results suggested that anti-BLV antibody levels in whey, measured by enzyme-linked immunosorbent assay, may be a useful marker to diagnose the risk of BLV infection and estimate PVL in blood and milk.